Evaluation of Antioxidative and Cytotoxic Activities of Streptomyces pluripotens MUSC 137 Isolated from Mangrove Soil in Malaysia - Ser, Hooi-Leng; Ab Mutalib, Nurul-Syakima; Yin, Wai-Fong; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2015)
A well characterized strain, Streptomyces pluripotens MUSC 137 was isolated from mangrove soil at Tanjung Lumpur, Malaysia. The biological activities of this particular strain of Streptomyces were then explored. For experimentation, the extract of fermentation was prepared by using solvent extraction method. The antioxidant activity was examined by using DPPH assay. The cytotoxicity activity of extract was assessed against selected human cancer cell lines, namely colon cancer cells (HCT-116, Caco-2, SW480 & HT-29), breast cancer cell (MCF-7), lung cancer cell (A549), prostate cancer cell (DU145) and cervical cancer cell (Ca Ski). The results showed MUSC 137 extract possessed significant antioxidant activity and cytotoxic effect against some of the tested cancer cell lines. Lowest IC50 was recorded in MCF-7 cells (61.33 ± 17.10 µg/mL), followed by HCT-116 and A549. Subsequently, the extract was subjected to chemical analysis using GC-MS, which led to the identification of chemical constituents present in the extract of MUSC 137. The analysis resulted in the identification of chemical constituents including deferoxamine and pyrrolizidines related-compounds which may responsible for antioxidant and cytotoxic activities observed. The result of the present investigation is the first report on the potential antioxidative and cytotoxic activities of Streptomyces pluripotens MUSC 137.